Elimination of Calm1 long 3′-UTR mRNA isoform by CRISPR–Cas9 gene editing impairs dorsal root ganglion development and hippocampal neuron activation in mice - Bae, Bongmin; Gruner, Hannah N.; Lynch, Maebh; Feng, Ting; So, Kevin; Oliver, Daniel; Mastick, Grant S.; Yan, Wei; Pieraut, Simon; Miura, Pedro (RNA (Cambridge), 2020)
The majority of mouse and human genes are subject to alternative cleavage and polyadenylation (APA), which most often leads to the expression of two or more alternative length 3′ untranslated region (3′-UTR) mRNA isoforms. In neural tissues, there is enhanced expression of APA isoforms with longer 3′-UTRs on a global scale, but the physiological relevance of these alternative 3′-UTR isoforms is poorly understood. Calmodulin 1 ( Calm1) is a key integrator of calcium signaling that generates short ( Calm1-S ) and long ( Calm1-L ) 3′-UTR mRNA isoforms via APA. We found Calm1-L expression to be largely restricted to neural tissues in mice including the dorsal root ganglion (DRG) and hippocampus, whereas Calm1-S was more broadly expressed. smFISH revealed that both Calm1-S and Calm1-L were subcellularly localized to neural processes of primary hippocampal neurons. In contrast, cultured DRG showed restriction of Calm1-L to soma. To investigate the in vivo functions of Calm1-L , we implemented a CRISPR–Cas9 gene editing strategy to delete a small region encompassing the Calm1 distal poly(A) site. This eliminated Calm1-L expression while maintaining expression of Calm1-S . Mice lacking Calm1-L ( Calm1 ΔL/ΔL ) exhibited disorganized DRG migration in embryos, and reduced experience-induced neuronal activation in the adult hippocampus. These data indicate that Calm1-L plays functional roles in the central and peripheral nervous systems.